Online platforms: concept, role in the conclusion of contracts and current legal framework in Europe - Campos Carvalho, Joana (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Companies like Airbnb, Amazon or Craigslist have challenged the traditional business models and are altering the way people have access to goods and services. This article explores why the concept of online platform is adequate to analyse this new reality from a contractual point of view. It then challenges the idea that all companies where the product or service is supplied by what appears to be a third-party are online platforms, using the example of Uber. Finally, it provides a brief overview at the current EU framework to provide a reflection on how a regime for online platforms could look like.
Keywords: sharing economy; online platforms; Uber